The impact of RF wattage level on local impedance and procedural parameters in AF ablation cases. (19th May 2022) - Meynet, I; Stabile, G; Mantica, M; Ferraro, A; D'ammando, M; Scaglione, M; Di Cori, A; Schillaci, V; Ottaviano, L; Mantovan, R; Ferrari, F; Bianchi, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Local impedance (LI) measurement can provide information on catheter tip contact, but also changes in LI during ablation can inform the extent and effectiveness of RF energy delivery. To date the relationship between highly LI measurements and contact force (CF) during atrial fibrillation (AF) ablation at different levels of energy delivery is still lacking. Purpose: We aimed to evaluate the impact of power setting on LI and key procedural parameters in AF ablation cases. Methods: A novel CF ablation catheter equipped with dedicated algorithm was used to measure LI at the distal electrode of this catheter. Radiofrequency (RF) catheter applications ≥45 watts were categorized as high power (HP) and applications <45w as standard power (SP). Ablations were also grouped according to different levels of CF (<5g, 5-14g, 15-24g and ≥25g). Data are reported as mean±SD. Results: Sixty-two consecutive pts undergoing RF catheter ablation of AF from the CHARISMA registry were included A total of 4619 ablation spots performed around PVs were analyzed (58% paroxysmal, 84% de novo, RF deliveries per pt=76±27, RF delivery time=9.1±5s, CF=12.3±8g). The majority of these were HP applications (n=4192, 91%). The mean LI was 158±17Ω prior to ablation and 138±14Ω after ablation (p<0.0001, absolute LI drop of 21.9±8Ω) with a LI drop rate equal to 4.4±3Ω/s. HP ablations had significantly shorter RF delivery times, 8.8±4s vs 12±7s (p<0.0001), larger LI drops (22.2±8Ω vs 19.3±9Ω, p<0.0001) and higher LI drop rates (4.5±3Ω/s vs 3.6±2Ω/s, p<0.0001) than SP, respectively. For both HP and SP settings, the magnitude of LI drop increased and RF delivery time decreased with increasing amounts of CF. The largest differences between HP and SP were found when CF was <15g (RF delivery time: 9±5s at HP vs 12.9±7s at SP, percentage of difference 26.3%, p<0.0001; LI drop: 21.2±8Ω at HP vs 18.6±9Ω, percentage of difference -14.3%, p<0.0001). No major complications occurred during the procedures. All PVs were successfully isolated. Conclusions: This preliminary experience suggests that, HP ablation is effective and safe and resulting in shorter RF delivery times and larger LI drops than SP ablation.